Electroactive Biomaterials for Facilitating Bone Defect Repair under Pathological Conditions. Issue 2 (1st December 2022) - Heng, Boon Chin; Bai, Yunyang; Li, Xiaochan; Lim, Lee Wei; Li, Wang; Ge, Zigang; Zhang, Xuehui; Deng, Xuliang
Abstract: Bone degeneration associated with various diseases is increasing due to rapid aging, sedentary lifestyles, and unhealthy diets. Living bone tissue has bioelectric properties critical to bone remodeling, and bone degeneration under various pathological conditions results in significant changes to these bioelectric properties. There is growing interest in utilizing biomimetic electroactive biomaterials that recapitulate the natural electrophysiological microenvironment of healthy bone tissue to promote bone repair. This review first summarizes the etiology of degenerative bone conditions associated with various diseases such as type II diabetes, osteoporosis, periodontitis, osteoarthritis, rheumatoid arthritis, osteomyelitis, and metastatic osteolysis. Next, the diverse array of natural and synthetic electroactive biomaterials with therapeutic potential are discussed. Putative mechanistic pathways by which electroactive biomaterials can mitigate bone degeneration are critically examined, including the enhancement of osteogenesis and angiogenesis, suppression of inflammation and osteoclastogenesis, as well as their anti‐bacterial effects. Finally, the limited research on utilization of electroactive biomaterials in the treatment of bone degeneration associated with the aforementioned diseases are examined. Previous studies have mostly focused on using electroactive biomaterials to treat bone traumatic injuries. It is hoped that this review will encourage more research efforts on the use of electroactive biomaterials for treating degenerative bone conditions. Abstract : Various diseases such as type II diabetes, osteoporosis, periodontitis, osteoarthritis, rheumatoid arthritis, osteomyelitis, and metastatic osteolysis can lead to bone degenerative conditions. Electroactive scaffolds can promote bone regeneration under pathological conditions by recapitulating the natural electrophysiological microenvironment of healthy bone tissues. This is achieved through enhancement of osteogenesis and angiogenesis, suppression of inflammation and osteoclastogenesis, as well as anti‐bacterial effects.